2021
DOI: 10.1111/bjd.19808
|View full text |Cite
|
Sign up to set email alerts
|

Inducible skin‐associated lymphoid tissue (iSALT) in a patient with Schnitzler syndrome who manifested wheals on recurrent localized erythema

Abstract: is 265 times the current exposure limit value of 23 mJ cm À2 at 222 nm. 7 Therefore, even at very high exposure doses, appropriately filtered far-UVC is unlikely to present a carcinogenic risk through direct DNA damage. These important but preliminary results are very encouraging. As recently advised and encouraged by the UK's Scientific Advisory Group for Emergencies we are continuing with multiple far-UVC research projects to investigate the efficacy and safety profile of this very promising technology. 8 Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Our case demonstrated a perivascular infiltration of neutrophils in the upper dermis, and lymphoid follicles with some plasma cells at the periphery only in the deeper dermis. 2 Castleman disease is classified into several subtypes depending on the clinical findings, and any subtype manifests lymphadenopathy, which was not detected by ultrasound and positron emission tomography/computed tomography in our patient. 3 Although Castleman disease usually exhibits IgG gammopathy, a subtype of POEMS (polyneuropathy, organomegaly, endocrinopathy, M protein, and skin changes) syndrome-associated multicentric Castleman disease is reported to display IgM monogammopathy, which was observed in our patient.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…Our case demonstrated a perivascular infiltration of neutrophils in the upper dermis, and lymphoid follicles with some plasma cells at the periphery only in the deeper dermis. 2 Castleman disease is classified into several subtypes depending on the clinical findings, and any subtype manifests lymphadenopathy, which was not detected by ultrasound and positron emission tomography/computed tomography in our patient. 3 Although Castleman disease usually exhibits IgG gammopathy, a subtype of POEMS (polyneuropathy, organomegaly, endocrinopathy, M protein, and skin changes) syndrome-associated multicentric Castleman disease is reported to display IgM monogammopathy, which was observed in our patient.…”
mentioning
confidence: 60%
“…On the other hand, the administration of anakinra demonstrated prompt favourable responses to clinical manifestations. 2 Taken together, although the possibility of Castleman disease and cutaneous plasmacytosis cannot be completely excluded, our case is considered as Schnitzler syndrome.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…Our group recently reported that lymphoid follicles in the skin exhibit immunohistochemical patterns analogous to those of lymph nodes, and therefore we defined these follicles as iSALT in humans (26)(27)(28)(29)(30). Similarly, many lymphoid follicles that fulfill the definition of TLS in histology-based studies have been identified in the salivary duct, in lachrymal drainage, in the Eustachian tube, and in the larynx (31).…”
Section: Definitions Of Malt and Tertiary Lymphoid Structures (Tlss)mentioning
confidence: 97%